The genus Platytenerus Miyatake, 1985 (Coleoptera: Cleridae: Neorthopleurinae), with description of a new species from Japan - Murakami, Hiroyuki (Zootaxa, 2015)
The genus Platytenerus Miyatake, 1985 (Coleoptera: Cleridae) is redescribed and classified into the subfamily Neorthopleurinae Opitz, 2009. A phylogenetic tree is supplementally provided for Platytenerus based on twenty morphological and two geographical characters. A new species of the genus, Platytenerus iriomotensis sp. n. is described from Iriomote Island, Okinawa, Japan.